Trato familiar y las habilidades socio emocionales en los niños de la Institución Educativa Inicial n° 259 Gotitas de Amor, Nauta 2022 - Silvano Tamani, Luz Magaly (2023)
The primary purpose of the study was to determine the connection between family treatment and the socio-emotional skills of children who attend the Initial Educational Institution No. 259 Gotitas de Amor in Nauta 2022. A quantitative approach was used, with a non-experimental, correlational design. and transactional. The study included a sample of 120 children and their respective families. It was concluded that family treatment is significantly related to socio-emotional skills and its first dimensions social skills, skills to be friends, skills related to the feelings of the children of the initial educational institution studied.